The effect of paternal factors on perinatal and paediatric outcomes: a systematic review and meta-analysis. (15th February 2018) - Oldereid, Nan B; Wennerholm, Ulla-Britt; Pinborg, Anja; Loft, Anne; Laivuori, Hannele; Petzold, Max; Romundstad, Liv Bente; Söderström-Anttila, Viveca; Bergh, Christina
Abstract: BACKGROUND: Maternal factors, including increasing childbearing age and various life-style factors, are associated with poorer short- and long-term outcomes for children, whereas knowledge of paternal parameters is limited. Recently, increasing paternal age has been associated with adverse obstetric outcomes, birth defects, autism spectrum disorders and schizophrenia in children. OBJECTIVE AND RATIONALE: The aim of this systematic review is to describe the influence of paternal factors on adverse short- and long-term child outcomes. SEARCH METHODS: PubMed, Embase and Cochrane databases up to January 2017 were searched. Paternal factors examined included paternal age and life-style factors such as body mass index (BMI), adiposity and cigarette smoking. The outcome variables assessed were short-term outcomes such as preterm birth, low birth weight, small for gestational age (SGA), stillbirth, birth defects and chromosomal anomalies. Long-term outcome variables included mortality, cancers, psychiatric diseases/disorders and metabolic diseases. The systematic review follows PRISMA guidelines. Relevant meta-analyses were performed. OUTCOMES: The search included 14 371 articles out of which 238 met the inclusion criteria, and 81 were included in quantitative synthesis (meta-analyses). Paternal age and paternal life-style factors have an association with adverse outcome in offspring. This is particularly evident for psychiatric disorders such as autism, autism spectrum disorders and schizophrenia, but an association is also found with stillbirth, any birth defects, orofacial clefts and trisomy 21. Paternal height, but not BMI, is associated with birth weight in offspring while paternal BMI is associated with BMI, weight and/or body fat in childhood. Paternal smoking is found to be associated with an increase in SGA, birth defects such as congenital heart defects, and orofacial clefts, cancers, brain tumours and acute lymphoblastic leukaemia. These associations are significant although moderate in size, with most pooled estimates between 1.05 and 1.5, and none exceeding 2.0. WIDER IMPLICATIONS: Although the increased risks of adverse outcome in offspring associated with paternal factors and identified in this report represent serious health effects, the magnitude of these effects seems modest.